The Frog Prince: a reconstructed transposon from Rana pipiens with high transpositional activity in vertebrate cells - Miskey, Csaba (Oxford University Press, 2003)
Members of the Tc1/mariner superfamily of transposable elements isolated from vertebrates are transpositionally inactive due to the accumulation of mutations in their transposase genes. A novel open reading frame-trapping method was used to isolate uninterrupted transposase coding regions from the genome of the frog species Rana pipiens. The isolated clones were ∼90% identical to a predicted transposase gene sequence from Xenopus laevis, but contained an unpredicted, ∼180 bp region encoding the N-terminus of the putative transposase. None of these native genes was found to be active. Therefore, a consensus sequence of the transposase gene was derived. This engineered transposase and the transposon inverted repeats together constitute the components of a novel transposon system that we named Frog Prince (FP). FP has only ∼50% sequence similarity to Sleeping Beauty (SB), and catalyzes efficient cut-and-paste transposition in fish, amphibian and mammalian cell lines. We demonstrate high-efficiency gene trapping in human cells using FP transposition. FP is the most efficient DNA-based transposon from vertebrates described to date, and shows ∼70% higher activity in zebrafish cells than SB. Frog Prince can greatly extend our possibilities for genetic analyses in vertebrates.